Conceptualization and Development of the Leg Activity Measure (LegA) for Patient and Carer Reported Assessment of Activity in the Paretic Leg. (16th February 2016) - Ashford, Stephen; Jackson, Diana; Mahaffey, Patrick; Vanderstay, Roxana; Turner‐Stokes, Lynne
Abstract: Background and Purpose: The purpose of the paper is to develop a patient‐reported outcome measure of active and passive function in the paretic lower limb with associated spasticity. Methods: Potential items for inclusion were identified through (1) systematic review and analysis of existing measures and (2) analysis of the primary goals for treatment in a spasticity service. Ethical approval for re‐evaluation of routinely collected data was received. Item reduction was achieved through consultation with a purposively selected group of experienced physiotherapists and occupational therapists ( n  = 16) in a two‐round Delphi process. This was followed by a review of Delphi consultation findings by the Project Advisory Group consisting of patients and carers. Results: Development of the leg activity measure (LegA) included two rounds of Delphi consultation, which resulted in a high degree of agreement (80% in round 2) between respondents in rounds 1 and 2. From an initial shortlist of 126 items, 29 items were initially identified for inclusion in LegA and subsequently refined to a 24‐item (two sub‐scales) tool consisting of nine passive function and 15 active function items. Discussion: The Delphi consultation with clinicians experienced in this area of practice ensured content validity and appropriate reduction of items. In common with previous work in the upper limb, a 5‐point ordinal scaling structure was chosen, with ratings based on activity over the preceding 7 days. The LegA is designed to measure passive and active function following focal interventions associated with spasticity in the lower limb. Content and face validity have initially been addressed within the development process. The next phase of development will involve formal evaluation of psychometric properties. Copyright © 2016 John Wiley & Sons, Ltd.